Menguji Kepemimpinan Kepala Desa dalam Pembangunan Infrastruktur Desa Rianiate Kecamatan Pangururan Kabupaten Samosir - Monita Oktavia; Prayetno Prayetno (Mahesa Research Center, 2018)
This article aims to present the condition of infrastructure development in Rianiate village under the leadership of the village head in developing village infrastructure. One indicator of the success of infrastructure development in a village depends on the role of the village head in fostering and involving community participation. The village head must be able to carry out his function as a motivator, facilitator, apply the principles of transparency, discipline, fairness and responsibility in carrying out village development tasks. Development in Desa Rianiate is already quite good, although there are still some shortcomings. The leadership of the village head in general is good even though it is still not optimal. The leadership was inherent in the village head of Rianiate. On the other hand, findings in the field are still found by some people who are reluctant to get involved with the tendency to prioritize personal matters.